Three novel sooty moulds species of Trichomerium from Yunnan, China - Yang, Hui; Maharachchikumbura, Sajeewa S.n.; Deng, Chao; Liu, Jian-Kui (Phytotaxa, 2021)
Collection of three sexual morphic fungal species occurring on the leaf surface of three plant species (Dalbergia obtusifolia, Syzygium fluviatile and Ziziphus mauritiana) collected in Yunnan Province, China, have shown that they are morphologically distinct. Phylogenetic analyses of partial sequences of internal transcribed spacer region (ITS) and large subunit rDNA (LSU) placed the three species in Trichomerium (Trichomeriaceae) but are sufficiently different from all known species. Therefore, three new species, Trichomerium multisetosum, T. xishuangbannaense and T. yunnanense are described with detailed, illustrated descriptions and notes.